Surgical treatment of left ventricular aneurysm of posterior basal localization - V.I. Ursulenko; О.K. Gogaeva; L.V. Jacob; M.L. Rudenko; N.M. Verich (Кардіохірургія та інтервенційна кардіологія)
The aim – to study the frequency and clinical features of the posterior basal left ventricular aneurysms, substantiate indications for their resection and to evaluate the efficiency of the developed technique of resection of the way from the «inside». Materials and methods. Among 11 thousands consecutive coronary artery bypass grafting (CABG) surgeries on the beating heart performed in 2000–2015, there were 136 with posterior basal aneurysm. In 51 cases aneurysm resection was not carried out due to small size and consistency of the aneurysm wall; in 85 patients CABG was combined with aneurysmectomy. The incidence of aneurysms of the posterior basal localization in the structure of aneurysms overall was 6.9 %. The need of resection has been shown only 4.3 % of cases. The method of clipping aneurysms from «inside» and plastics of left ventricular defect followed by tight stitching aneurysm sac was developed. Results. The efficiency of the developed technique of aneurysm resection and plastics was studied by intraoperative data, ECG, echocardiography and computer tomography heart catheteterization, markers of myocardial damage. Evaluating the effectiveness of the developed method of surgical treatment of this pathology has shown its simplicity and efficiency, significant decrease of left ventricular end-diastolic dimension, accompanied increase of ejection fraction by 27,0 %. Control ventriculography showed a good effect on the recovery of left ventricular geometry. Conclusions. Indications for small posterior basal aneurysm elimination, in the absence of clots and mitral insufficiency are relative and depend on the nature of the walls of the aneurysm dome. The developed method of clipping aneurysms is characterized by simplicity and affordability, provides good effect regarding recovery of left ventricular geometry and improves its systolic function.